A Versatile Theranostic Nanoemulsion for Architecture‐Dependent Multimodal Imaging and Dually Augmented Photodynamic Therapy. Issue 21 (25th March 2019) - Zhang, Yifan; Bo, Shaowei; Feng, Tao; Qin, Xialing; Wan, Yilin; Jiang, Shanshan; Li, Chunxiao; Lin, Jing; Wang, Tianfu; Zhou, Xin; Jiang, Zhong‐Xing; Huang, Peng
Abstract: To design a clinically translatable nanomedicine for photodynamic theranostics, the ingredients should be carefully considered. A high content of nanocarriers may cause extra toxicity in metabolism, and multiple theranostic agents would complicate the preparation process. These issues would be of less concern if the nanocarrier itself has most of the theranostic functions. In this work, a poly(ethylene glycol)‐boron dipyrromethene amphiphile (PEG‐F54 ‐BODIPY) with 54 fluorine‐19 ( 19 F) is synthesized and employed to emulsify perfluorohexane (PFH) into a theranostic nanoemulsion (PFH@PEG‐F54 ‐BODIPY). The as‐prepared PFH@PEG‐F54 ‐BODIPY can perform architecture‐dependent fluorescence/photoacoustic/ 19 F magnetic resonance multimodal imaging, providing more information about the in vivo structure evolution of nanomedicine. Importantly, this nanoemulsion significantly enhances the therapeutic effect of BODIPY through both the high oxygen dissolving capability and less self‐quenching of BODIPY molecules. More interestingly, PFH@PEG‐F54 ‐BODIPY shows high level of tumor accumulation and long tumor retention time, allowing a repeated light irradiation after a single‐dose intravenous injection. The "all‐in‐one" photodynamic theranostic nanoemulsion has simple composition, remarkable theranostic efficacy, and novel treatment pattern, and thus presents an intriguing avenue to developing clinically translatable theranostic agents. Abstract : A versatile theranostic nanoemulsion is synthesized by using a PEG‐F54 ‐BODIPY amphiphile as the emulsifier. Taking advantage of the delicate interactions of the nanocarrier and interior perfluorocarbon, both architecture‐dependent trimodal imaging and highly efficient photodynamic therapy are achieved.